ISLAMIC EDUCATION IN PLURALITY DISCOURSE STATE INSTITUTE FOR ISLAMIC STUDIES (IAIN) SALATIGA - Mukh Nursikin (Pascasarjana IAIN Metro, 2019)
The differences of views about Islam is single or plural impact on the debate on the use of terminology of Indonesia Islamic education. This debate on terminology actually arose among the Muslims who have more understanding about the conception of Islamic education. Therefore, this study aims to explore the attitudes of the academic community of the Faculty of Tarbiyah and Science Teachers (FTIK) of the State Islamic Institute (IAIN) Salatiga against the use of Islamic education terminology in Indonesia, so as to know the views of respondents about Islam is single or plural. This research uses quantitative descriptive research type. The population of this study are students of the third semester and the fifth semester at the State Islamic Institute (IAIN) at Tarbiyah and Science Teachers (FTIK) Salatiga as many as 1763 respondents. Researcher took 355 samples of respondents with cluster random sampling technique. Data collection use questioner method. Data were analyzed with descriptive statistics. The data that has been collected then followed the stages of description, reduction, selection, discussion, analysis and conclusions. This research concluded that the majority of the academic community of the State Islamic Institute (IAIN) Salatiga were disagree with the terminology of Islamic education of Indonesia. They are more amenable to use the term Islamic education in Indonesia. This shows that the academic community of the Faculty of Tarbiyah and Science Teachers (FTIK) of the State Islamic Institute (IAIN) Salatiga views that Islam as single rather than plural. The study also found that respondents who have more understanding about the conception of Islamic education who reject the terminology of Islamic education in Indonesia are greater than those who have less understanding of the conception of Islamic education. Therefore, it is suspected that there is a negative correlation between the level of understanding of the concept of Islamic education with plurality attitude.